Thinking about cognition - Galavan, Robert; Sund, Kristian J., 1975- (Emerald Publishing Limited, 2021)
The broad field of managerial and organizational cognition (MOC) has diversified over the years. Where early studies of MOC focused on theories of rational conscious thought, illustrated for example by schema theory, over the years we have seen explorations of unconscious processing, heuristics and cognitive biases, along with emotions, identity, and the 'darker' sides of cognition. Thinking About Cognition takes stock by reflecting on the frontiers of the field and addressing the future beyond our current state-of-the-art. The result is a collection of papers reflects emerging research in the field of cognition and considers developments in mindfulness, networked societies, neuropsychology, identity theory, team cognition, decision making, distant futures, cultural and ethnic backgrounds, change, and agency. This fifth anniversary volume of New Horizons in Managerial and Organizational Cognition comprises of a collection of contributions that discuss frontiers of MOC research, address the challenges we face, inspire other scholars, and provide guidance on how to proceed.
Keywords: Psychology, Industrial.; Cognition.; Psychology -- Industrial & Organizational Psychology.; Occupational & industrial psychology.; elektronické knihy; electronic books